Characterization of hydroxypropyl-β-cyclodextrins with different substitution patterns via FTIR, GC–MS, and TG–DTA. (15th March 2015) - Yuan, Chao; Liu, Benguo; Liu, Hui
Highlights: The structure and the thermal properties of hydroxylpropyl-β-cyclodextrins were evaluated. The DS value increased according to the quantity of propylene oxide and the substitution pattern depends on the alkali conditions. The thermal decomposition temperature of HPCDs was enhanced linearly as the molecular DS increased. Abstract: The structure and thermal properties of hydroxylpropyl-β-cyclodextrins (HPCDs) with different degrees of substitution (DS) and different substitution sites were evaluated via GC–MS, FTIR, and TG–DTA combined thermoanalytical techniques. The results of GC–MS provided the DS and substitution pattern of the HPCD samples. The IR spectra of HPCDs showed all characteristic peaks corresponding to cyclodextrin. Furthermore, the characteristic peaks for methyl in the hydroxypropyl group at 2960 and 1375 cm −1 were observed. The thermal decomposition temperature of HPCDs was about 300 °C to 400 °C and enhanced linearly as the molecular DS increased. The rate of DS rise of HPCDs prepared at a strong alkaline condition was higher than that prepared in a weak alkaline solution.